(untitled) (Research, Society and Development, 2022)
It is possible to see that with the transformations of current society, such as exacerbated individualism, the cult of the body and the image, social relations are easily constructed and deconstructed, as the bonds are fragile and superficial. However, despite all the changes, love survives intensely between the places of social responsibilities. Thus, the research stands out as a qualitative, quantitative and descriptive study, with the general objective of understanding the meaning of love, for different social actors, in different contexts. The specific objectives are: to identify social, community, business and religious leaders in the research territory as social actors; identify the characteristics most commonly attributed and/or associated with the word love by different social actors and compare the similarities and differences in the meanings of love for different social actors. The results of the research induced that despite the meanings of love being related to the life experience of each participant, all agreed that it is a positive feeling, and for most, the most important feeling in life, so one can think that by love being a unique experience that allows subjectivity to be present, its presence would favor a decentralization of attention focused on the external, and the exacerbation of corporate affections and feelings, building more solid and specific social relationships, therefore, the obligations on " love” are of great importance for the development of subsidies for proposals to encourage moral values.